Understanding renal nuclear protein accumulation : an in vitro approach to explain an in vivo phenomenon - Luks, Lisanne; Maier, Marcia Y.; Sacchi, Silvia; Pollegioni, Loredano; Dietrich, Daniel R. (My University, 2017)
Proper subcellular trafficking is essential to prevent protein mislocalization and aggregation. Transport of the peroxisomal enzyme d-amino acid oxidase (DAAO) appears dysregulated by specific pharmaceuticals, e.g., the anti-overactive bladder drug propiverine or a norepinephrine/serotonin reuptake inhibitor (NSRI), resulting in massive cytosolic and nuclear accumulations in rat kidney. To assess the underlying molecular mechanism of the latter, we aimed to characterize the nature of peroxisomal and cyto-nuclear shuttling of human and rat DAAO overexpressed in three cell lines using confocal microscopy. Indeed, interference with peroxisomal transport via deletion of the PTS1 signal or PEX5 knockdown resulted in induced nuclear DAAO localization. Having demonstrated the absence of active nuclear import and employing variably sized mCherry- and/or EYFP-fusion proteins of DAAO and catalase, we showed that peroxisomal proteins ≤134 kDa can passively diffuse into mammalian cell nuclei—thereby contradicting the often-cited 40 kDa diffusion limit. Moreover, their inherent nuclear presence and nuclear accumulation subsequent to proteasome inhibition or abrogated peroxisomal transport suggests that nuclear localization is a characteristic in the lifecycle of peroxisomal proteins. Based on this molecular trafficking analysis, we suggest that pharmaceuticals like propiverine or an NSRI may interfere with peroxisomal protein targeting and import, consequently resulting in massive nuclear protein accumulation in vivo.
Keywords: Protein accumulation, Protein trafficking, Peroxisomal proteins, Nuclear diffusion, d-amino acid oxidase, Propiverine; 570